CONVERGING OF THE INSURANCE, BANKING AND CAPITAL MARKETS - Hague, Ken (Assurances)

(untitled) (HEC Montréal, 1999)
The pressure for profits in the financial services sector is causing a convergence of services and products. Striving to achieve economies of scale and seeking to satisfy as many of their clients’ needs as possible, the insureers, banks and capital markets are all crossing the boundaries into each other’s sphere of operation.